2004
DOI: 10.1248/bpb.27.1397
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of the Toxicity of 2,3,7,8-Tetrachlorodibenzo-p-dioxin in Mice Using an Antiulcer Drug, Geranylgeranylacetone

Abstract: The protective effect of geranylgeranylacetone (GGA), an antiulcer drug, against the acute toxicity and teratogenicity produced by 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) was examined in C57BL/6J mice. When mice were co-treated, GGA reduced the loss of body weight gain and lethality produced by TCDD but hepatomegaly and thymic atrophy were not improved. Additionally, no protective effect of GGA was observed in the formation of cleft palate and hydronephrosis in mouse fetuses caused by maternal exposure to T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
1
5
1
Order By: Relevance
“…Thus, GGA pretreatment quickly and transiently elevated the expression of HSP70 protein in eyes. These results are consistent with a previous study examining other organs (Ishida et al, 2004).…”
Section: Article In Presssupporting
confidence: 94%
“…Thus, GGA pretreatment quickly and transiently elevated the expression of HSP70 protein in eyes. These results are consistent with a previous study examining other organs (Ishida et al, 2004).…”
Section: Article In Presssupporting
confidence: 94%
“…In general, while the expression of Hsps is very low under normal physiological conditions, 22) those proteins are induced by various stresses such as stimuli by xenochemicals. 23) Although we previously reported the induction of hepatic Hsp70 by dioxins, 4,5) one of our previous studies performed with the same dose and schedule of TCDD administration as the present study also failed to show any notable TCDD-dependent increase in Hsp70.1 mRNA.…”
Section: Discussioncontrasting
confidence: 57%
“…This is partially supported by our previous observation that geranylgeranylacetone and curcumin, potent inducers of Hsp70, significantly attenuated the reduction in body weight gain and lethality in C57BL/6J mice produced by TCDD. 5,6) Flavonoids are thought to improve health, and this effect seems to be due at least partially to their antioxidant effects. Diets rich in phenolic flavonoids such as quercetin reduce the risk of chronic degen- To clarify the relationship between heat shock protein (Hsp) 70 expression and dioxin toxicity, we studied the effect of quercetin, which is an inhibitor of the biosynthesis of Hsp70, on the acute toxicity of 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) in C57BL/6J mice.…”
Section: Introductionmentioning
confidence: 99%
“…The studies presented herein examined the impact of a relatively high dose (10 μg/kg) of TCDD compared to human background levels. However, the dose of TCDD used in the present study was similar to that reported by other investigators [56][57][58] and was chosen to insure that we could identify appropriate endpoints in offspring animals. Importantly, humans are exposed to complex mixtures of toxicants which are collectively capable of interacting with the AhR [59].…”
Section: Discussionmentioning
confidence: 99%